Réponses

2014-04-16T19:06:56+02:00
1)
A =  \frac{6}{5} -  \frac{17}{14} ÷  \frac{5}{7}
A =  \frac{6}{5} -  \frac{17}{14} *  \frac{7}{5}
A =  \frac{6}{5} -  \frac{119}{70}
A =  \frac{6*14}{5*14} -  \frac{119}{70}
A =  \frac{84}{70} -  \frac{119}{70}
A = - \frac{35}{70}  = - \frac{5}{14}

2)
B =  \frac{8*10^{8}*1.6 }{0.4*10^{-3} }
B =  \frac{1.28*10^{1} *10^{8}  }{4*10^{-3} }
B =  \frac{1.28*10^{9} }{4*10^{-4} }
B = 3.2 * 10^{12}

3)
C = ( \sqrt{5} +  \sqrt{10} )^{2}  - 10 \sqrt{2}
C =  \sqrt{5}^{2} + 2*  \sqrt{5*10} +  \sqrt{10}^{2} - 10 \sqrt{2}
C = 5 + 2 \sqrt{50} + 10 - 10 \sqrt{2}
C = 15 + 2 \sqrt{25*2}  - 10 \sqrt{2}
C = 15 + 2*5 \sqrt{2} - 10 \sqrt{2}
C = 15 + 10 \sqrt{2} - 10 \sqrt{2}   ⇒ Les deux s'annulent
C = 15
La première ligne du 1) c'est un divisé juste après la fraction 17 sur 14